Law Enforcement Of The Criminal Action Of Drug Distribution According To Law No. 35 Of 2009 (Case Study Of Polres Semarang) - Azis Budianto; Rineke Sara; Suyatin Suyatin (Journal Research of Social Science, Economics, and Management, 2023)
Policing opiates violations has been completed by various policemen and has gotten many adjudicator's choices. Policing be an impediment to the expansion in unlawful exchange and dissemination of opiates, however truly, the more concentrated policing did, the more dispersion and illegal exchange of opiates will likewise increment. Official arrangements overseeing opiates issues have been drafted and authorized, be that as it may, offenses connected with opiates have not been mollified. These last cases have gotten many street pharmacists and vendors and got serious assents, yet different culprits appear to disregard them and, surprisingly, will generally grow their area of activities. The narcotics crime referred to in Law Number 35 of 2009 concerning Narcotics provides for quite severe criminal sanctions, however, in reality, the number of perpetrators of crimes is increasing, and convicts, in reality, are not deterred that there is a tendency to repeat them. It is caused by criminal imposition factors that existed and have no impact or deterrent effect on the perpetrators. Law Number 35 of 2009 is no longer based on the imposition of punishment for each drug abuse which is felt to be less effective in eradicating or reducing narcotics crimes.